The biliary tree musketeers: cholangiocarcinoma - one name for all, but at least three different diseases with distinct targets - Lidiane Vieira Marins; Camila Motta Venchiarutti Moniz; Cecília Souza Freire; Antonio Hugo José Fróes Marques Campos (BMC, 2024)
Abstract Cholangiocarcinoma, a malignant neoplasm of the biliary system, poses a significant challenge in clinical practice due to its increasing incidence and diagnostic and therapeutic complexity. This review addresses the epidemiological aspects, risk factors, and classification of this disease. We examine advances in histological diagnosis, highlighting essential criteria for accurate assessment. Additionally, we discuss standard treatment approaches and their efficacy, alongside the latest innovations in therapy, including emerging biomarkers and targeted therapies. By providing a comprehensive overview of these topics, this article aims to enhance understanding and guide the pathological diagnosis and clinical management of this devastating disease.